Causes and consequences of eastern Australia's 2019–20 season of mega‐fires. (22nd January 2020) - Nolan, Rachael H.; Boer, Matthias M.; Collins, Luke; Resco de Dios, Víctor; Clarke, Hamish; Jenkins, Meaghan; Kenny, Belinda; Bradstock, Ross A.
Abstract : See Letter to the Editor on this article by Adam et al ., 26, 3756–3758 . See also Response to the Letter by Bradstock et al ., 26, e8–e9 .